2013
DOI: 10.11607/jomi.2668
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia and Titanium Implant Abutments for Single-Tooth Implant Prostheses After 5 Years of Function in Posterior Regions

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 0 publications
4
78
0
7
Order By: Relevance
“…Zirconia has better mechanical properties than all of the previously introduced ceramics 3) . Furthermore, much clinical research into zirconia-based all-ceramic restorations has confirmed that zirconia ceramics exhibit high stability as a frame work material for full coverage crowns [4][5][6][7] , fixed partial dentures (FPDs) 5,[8][9][10][11] , and implant abutments [12][13][14] . It has often been reported that full-coverage zirconia ceramic restoration and FPDs might not require adhesive cementation and that they can be cemented with conventional cements, including zinc phosphate 4,6,8,11) or glass ionomer cement 5,10) .…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia has better mechanical properties than all of the previously introduced ceramics 3) . Furthermore, much clinical research into zirconia-based all-ceramic restorations has confirmed that zirconia ceramics exhibit high stability as a frame work material for full coverage crowns [4][5][6][7] , fixed partial dentures (FPDs) 5,[8][9][10][11] , and implant abutments [12][13][14] . It has often been reported that full-coverage zirconia ceramic restoration and FPDs might not require adhesive cementation and that they can be cemented with conventional cements, including zinc phosphate 4,6,8,11) or glass ionomer cement 5,10) .…”
Section: Introductionmentioning
confidence: 99%
“…3) Results of the Effect of metallic and nonmetallic implant abutment on rescission index :-Examination of rescission index around Zirconia and Titanium abutments was reported in four studies. showing mean values at Zirconia abutments ranged from 0 to 0.3 and at Titanium abutments ranged from 0 to 0.4, after 6months the mean of recession index around Zirconia abutment was 0.16 while for titanium abutment was 0.27 (15).later 1 year follow up the mean of recession index around Zirconia abutment was zero while for titanium abutment was 0.04 (12) , furthermore increasing the recession was reported after 2 year follow up for Zirconia to range from 0.3 and was 0.4 for titanium abutment (10),additionally the mean of recession index around Zirconia abutment ranged from 0.1-0.3 whereas for titanium abutment was from 0.3-0.4 after 3y and 5y follow up (8,11) with no significant differences between them .…”
Section: Results Of the Effect Of Metallic And Nonmetallic Implant Abmentioning
confidence: 97%
“…This action can be claimed; though, patient bias is avoidable through uncontrolled prospective clinical trials. Therefore, the longest follow-up included was 5 years long (10,11). In general, the results of both abutment materials showed only minor statistically significant differences.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The following inclusion criteria 17 were considered: The presence of at least two posterior implants on two sides in the #6 or #7 areas in the same jaw, whose clinical success had been confirmed; the presence of at least 1 mm of attached gingiva around the implants; a maximum gingival thickness of 3 mm in the implant neck area; and a minimum age of 18 years.…”
Section: Inclusion Criteriamentioning
confidence: 99%